COMMUNITY EMPOWERMENT IN THE VILLAGE OF DUKUH KUPANG, SURABAYA, IN THE NATURAL DISASTER MITIGATION PROGRAM IN 2022 - Ardiansjah, Fahmi Fitra (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
The research conducted in this study aimed to investigate the influence of the Quality of Human Resources, Environment, and Group Support on the Community Empowerment of Dukuh Kupang Surabaya Village in the Natural Disaster Mitigation Program in 2022. The objective was to evaluate the level of preparedness of the Dukuh Kupang Village community in dealing with flood disasters through the implementation of disaster mitigation programs. To achieve this objective, the researchers selected a sample of 392 respondents who were residents of 8 Rukun Warga in Dukuh Kupang Surabaya Village. The sample was chosen using the Simple Random Sampling technique, ensuring that a diverse range of individuals from the community were included. The researchers distributed questionnaires to all respondents, which allowed them to collect data on various factors related to the Quality of Human Resources, Environment, Group Support, and Community Empowerment. The collected data was then analyzed using Multiple Linear Regression analysis, which enabled the researchers to test their hypotheses. The results of the analysis indicated that the Quality of Human Resources, Environment, and Group Support had a positive and significant impact on the Community Empowerment of Dukuh Kupang Surabaya Village in the Natural Disaster Mitigation Program in 2022. This means that individuals with higher levels of knowledge, skills, and abilities, as well as a supportive environment and group dynamics, were more likely to be empowered in dealing with natural disasters.